Fitomassa e acumulo de macronutrientes em cana-de-açúcar sob compactação e umidade do solo - Rossato, Otavio Bagiotto; Martello, Jorge Martinelli [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP] (My University, 2016)
The experiment was conducted in PVC tubes, in a greenhouse, using a randomized block design with four replications, in a factorial arrangement (4x3x2) equivalent to four varieties, three levels of soil compaction in the layer 0.20 to 0.30 m (1.35, 1.45 and 1.55 Mg m-3) and two soil moisture contents (70% and 90% of field capacity). 72 days after the plants emergence the dry mass of roots and shoots and N, P, K, Ca, Mg, S contents accumulated in shoots of sugarcane were assessed. The results show that the higher moisture level in the soil led to increases in dry matter production of shoots and roots besides higher accumulation of N, P, K, Ca, Mg and S in sugarcane shoots regardless of the variety and level of compaction. In addition, variety RB72454 provided greater shoots with dry matter and higher accumulation of N, P, K, Ca, Mg and S on shoots than in other varieties under greater availability of water in the soil. The highest level of soil compaction promoted reduction in shoot dry matter production and accumulation of N, P, K, Ca and Mg on shoots of sugarcane regardless of the variety used. On soils with lower water availability (70% of field capacity), the highest level of soil compaction (1.55 Mg m-3) promoted a reduction on shoot biomass production and accumulation of N, P, K, Ca and Mg.
Dry matter production and macronutrient accumulation in sugarcane grown under levels of compaction and soil moisture
Keywords: Density; Dry matter; Nutrients; Root; Saccharum spp; Shoot; Soil water content